2012
DOI: 10.1111/j.1750-3841.2012.02755.x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, Antihyperglycemic, and Antihyperlipidemic Effects of Coriandrum sativum Leaf and Stem in Alloxan‐Induced Diabetic Rats

Abstract: The leaves and stem of this plant Coriandrum sativum if used in cuisine would be a remedy for diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 25 publications
2
45
0
4
Order By: Relevance
“…The biological activity of essential oil of Coriandrum sativum seeds was tested against adult Tribolium confusum Duval (Coleoptera: Tenebrionidae) and Callosobruchus maculatus F. (Coleoptera: Bruchidae) in a series of laboratory experiments. The mortality of 1-7 day old adults of the insect pests increased with concentration from 43 to 357 μl/l air and with exposure time from 3 to 24 h. In the probit analysis, LC 50 values showed that C. maculatus (LC 50 = 1.34 μl/l air) was more susceptible than T. confusum (LC 50 = 318.02 μl/l air) to seed essential oil of Coriandrum sativum [106].…”
Section: Antibacterial Antifungal Anthelmintic and Insecticidal Effmentioning
confidence: 99%
See 3 more Smart Citations
“…The biological activity of essential oil of Coriandrum sativum seeds was tested against adult Tribolium confusum Duval (Coleoptera: Tenebrionidae) and Callosobruchus maculatus F. (Coleoptera: Bruchidae) in a series of laboratory experiments. The mortality of 1-7 day old adults of the insect pests increased with concentration from 43 to 357 μl/l air and with exposure time from 3 to 24 h. In the probit analysis, LC 50 values showed that C. maculatus (LC 50 = 1.34 μl/l air) was more susceptible than T. confusum (LC 50 = 318.02 μl/l air) to seed essential oil of Coriandrum sativum [106].…”
Section: Antibacterial Antifungal Anthelmintic and Insecticidal Effmentioning
confidence: 99%
“…The free radical scavenging effect of the extracts was comparable with that of the reference antioxidants. Furthermore, it also showed an improved antioxidant potential as evidenced by decreased lipid peroxidation and a significant increase in the activity of various antioxidant enzymes such as catalase, superoxide dismutase, and glutathione peroxidase in the liver of diabetic rats [50].…”
Section: Antidiabetic Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…Bunun yanında, çeşitli oksidatif stres hastalıkları için umut verici bir ilaç olup olamayacağı hakkında daha fazla çalışma gerektiği belirtilmiştir. Bu çalışmanın alloksan kaynaklı diyabetik sıçanlarda gözlenen antioksidan etki kapasitesi ile ilgili sonuçları, kişnişin yaprak ve saplarının diyabet tedavisine destek, iyi bir besin takviyesi olarak kullanılabileceğini de göstermiştir (63). Brindis ve arkadaşlarının 2014 yılında yaptığı bir çalışmada ise, in vivo ve in vitro analizler, kişnişin sulu ekstresinin antihiperglisemik etkisi, özellikle de bir flavonoid bileşiği olan rutinin glukozidaz aktivitesini inhibe ettiği gözlenmiş, bu sonuçlar ile de kişnişin antidiyabetik olarak kullanılabileceği bir kez daha kanıtlanmıştır (64).…”
Section: Antidiyabetik Etkiunclassified